2014
DOI: 10.1016/j.agee.2014.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Sources of sediment-bound organic matter infiltrating spawning gravels during the incubation and emergence life stages of salmonids

Abstract: Keywords:Sediment-bound organic matter Sources Carbon and nitrogen stable isotopes Near infra-red reflectance spectroscopy Salmonids Farm manures A B S T R A C TThe biodegradation of organic matter ingressing spawning gravels in rivers exerts an oxygen demand which is believed to contribute to detrimental impacts on aquatic ecology including salmonids. Catchment management strategies therefore require reliable information on the key sources of sediment-bound organic matter. Accordingly, a novel source fingerpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 76 publications
3
40
1
Order By: Relevance
“…The Modified MixSIR model uses Bayesian as opposed to frequentist distribution‐based principles, and predicted source proportions can be biased by the choice of sediment unmixing model structure (Laceby & Olley, ; Smith & Blake, ). Previous work has explored a range of weightings including those for tracer analytical precision (Collins et al, ) or discriminatory power (e.g., Collins et al, ) and spatial variations in tracers by source category (e.g., Gellis & Noe, ; Wilkinson et al, ) as well as corrections for particle size (Collins et al, ) or organic matter (e.g., Gellis & Noe, ) selectivity. Here, given the inherent uncertainties associated with these numerical model parameters (Koiter, Owens, Petticrew, & Lobb, ; Laceby et al, ), such additions to unmixing model structure were avoided.…”
Section: Resultsmentioning
confidence: 99%
“…The Modified MixSIR model uses Bayesian as opposed to frequentist distribution‐based principles, and predicted source proportions can be biased by the choice of sediment unmixing model structure (Laceby & Olley, ; Smith & Blake, ). Previous work has explored a range of weightings including those for tracer analytical precision (Collins et al, ) or discriminatory power (e.g., Collins et al, ) and spatial variations in tracers by source category (e.g., Gellis & Noe, ; Wilkinson et al, ) as well as corrections for particle size (Collins et al, ) or organic matter (e.g., Gellis & Noe, ) selectivity. Here, given the inherent uncertainties associated with these numerical model parameters (Koiter, Owens, Petticrew, & Lobb, ; Laceby et al, ), such additions to unmixing model structure were avoided.…”
Section: Resultsmentioning
confidence: 99%
“…The inclusion of both sub‐indices lends support to the arguments to take account of both the mineral and organic components of sediment stress on the aquatic environment (Collins et al ., , ) and properly addresses the definition of sediment stress in the EU WFD. Organic material can be introduced into the fine‐grained sediment load of river systems from a variety of sources, and recent studies have demonstrated fingerprinting procedures for apportioning such inputs (Collins et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Fine sediment can reduce light penetration and suppress primary production in algae and macrophytes (Izagirre, Serra, Guasch, & Elosegi, ; Jones, Collins, et al, ; Jones, Murphy, et al, ; Yamada & Nakamura, ). Deposited fine sediment can alter bed morphology and degrade habitat for macroinvertebrates (Jones, Collins, et al, ; Jones, Murphy, et al, ) and fish (Collins et al, ; Sear et al, ). In addition, fine sediment provides a transport vector for bound nutrients, heavy metals, and other contaminants (Owens et al, ), particularly from urban run‐off (Jartun, Ottesen, Steinnes, & Volden, ; Witter, Nguyen, Baidar, & Sak, ).…”
Section: Introductionmentioning
confidence: 99%